2002
DOI: 10.1089/15303660260613729
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Analysis of West Nile Virus: Rapid Risk Assessment of an Introduced Vector-Borne Zoonosis

Abstract: The distribution of human risk for West Nile virus was determined by spatial analysis of the initial case distribution for the New York City area in 1999 using remote sensing and geographic information system technologies. Cluster analysis revealed the presence of a statistically significant grouping of cases, which also indicates the area of probable virus introduction. Within the cluster, habitat suitability for potentially infective adult mosquitoes was measured by the amount of vegetation cover using satel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
93
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 130 publications
(99 citation statements)
references
References 25 publications
1
93
1
Order By: Relevance
“…27 In this study, we used 14 land cover classes 15 to characterize the landscape in different regions of the United States. West of the Mississippi River, the main mosquito vector of WNV is Cx.…”
Section: Discussionmentioning
confidence: 99%
“…27 In this study, we used 14 land cover classes 15 to characterize the landscape in different regions of the United States. West of the Mississippi River, the main mosquito vector of WNV is Cx.…”
Section: Discussionmentioning
confidence: 99%
“…The spatial resolution of human surveillance data did not allow for fi ner evaluation of within-urban associations. Brownstein et al linked human WNV cases to greenness indices in urban areas and found an optimal vegetation index associated with higher human cases (35). Brown et al found an environmental separation of bridge and enzootic vectors; bridge vectors occurred in areas with vegetation that might be associated with residential areas within a city (36).…”
Section: Discussionmentioning
confidence: 99%
“…Logistic regression modeling has been extensively used to formalize the relationship between environmental factors and the pres-ence/absence of vectors (Brownstein et al 2003, Dumonteil and Gourbiere 2004, Thomson et al 1999) and incidence of vector-borne diseases in humans (Brooker et al 2001, Elnaiem et al 2003, King et al 2004, Lindsay and Thomas 2000, Thompson et al 1996 and to quantify the amount of potential habitat. In this study, we did not use presence/absence but rather high/low mosquito abundance as the response variable.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach is to use landscape variables derived from remote sensing satellites as predictors, with or without incorporating the effects of spatial dependence. Pertinent examples include vectors of Eastern equine encephalomyelitis (Moncayo et al 2000), tick vectors of Lyme disease (Brownstein et al 2003, Guerra et al 2001, Kitron et al 1996, sand fly vectors of leishmaniasis (Cross et al 1996, Elnaiem et al 2003, Miranda et al 1998, Thomson et al 1999, tse-tse fly vectors of African trypanosomiasis (Kitron et al 1996, Rogers 2000, and mosquito vectors of malaria (Beck et al 1994, Diuk-Wasser et al 2004, Thomson et al 1996, Wood et al 1991a,b, 1992. Of these models, however, only a few have been validated with an independent dataset (Beck et al 1997, Brownstein et al 2004).…”
Section: Introduction Wmentioning
confidence: 99%